Macroeconomic principles and problems a pluralist introduction - Schneider, Geoffrey Eugene (Abingdon, Oxon Routledge, 2023)
Macroeconomic Principles and Problems: A Pluralist Introduction offers a comprehensive overview of the major topics in modern macroeconomics, from mainstream and heterodox perspectives. This textbook examines the key macroeconomic problems and policy debates facing contemporary society, including economic crises, sustainability, fiscal and monetary policy, government debt, state-led vs. market-led approaches for growth, and unregulated trade vs. protectionism. Written in an engaging style and focused on real-world examples, this textbook brings macroeconomics to life. Multiple examples of how each economic model works, coupled with critical analysis of the assumptions behind them, enable students to develop a sophisticated understanding of the material. Digital supplements are also available for students and instructors. Macroeconomic Principles and Problems offers the most contemporary and complete package for any pluralist macroeconomics class"--
Contents: PART 1: Economics: A Pluralist Definition - - What is economics? The answer depends on who you ask - - Scarcity, choice, and opportunity cost: The mainstream approach, the PPC model, the limits of this approach, and the importance of institutions - - PART 2: The evolution of economic ideas and systems: The evolution of economic systems and the ideas of Adam Smith: From communal societies to early capitalism - - Marx, Veblen, and the dark ages of capitalism: Historical materialism, the exploitation of labor, and monopoly capitalism - - Keynes and mixed market capitalism: How to save capitalism from itself - - Modern economic systems: Market-dominated, social market, and state-dominated economies - - Markets and how they work: The institutional foundations of markets and the supply and demand model - - PART 3: Macroeconomic issues and problems: Modern macroeconomics: The evolution of macroeconomic theory and the macroeconomy in the modern era - - Macroeconomic well-being: Measuring and describing the macroeconomic market failures - - PART 4: Macroeconomic models: Aggregate demand and aggregate supply: A mainstream economics model of the macroeconomy - - The Keynesian aggregate expenditure-income model: The foundation of modern macroeconomics - - PART 5: Stabilization policy: Fiscal policy, debt, and deficits: Fiscal activism vs. austerity and the macroeconomic role of government - - Money, banking, and the financial sector: How money markets make the world go around - - Monetary policy: The role of central banks in stabilizing economies and regulating financial markets - - Crises, financial and otherwise: On the causes and consequences of economic crises and how they can be averted - - PART 6: Growth and global interconnectedness: The sources of economic growth - - International trade and integration: How unregulated trade, protectionism, and trade agreements affect economies - - International finance and open economy macroeconomics: Exchange rates, financial flows, and the balance of payments - - Economic development: The barriers facing less developed countries and how they can be overcome.
Includes bibliographical references and index.
Keywords: Macroeconomics